2015
DOI: 10.1158/0008-5472.can-15-1107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of P450 Oxidoreductase as a Major Determinant of Sensitivity to Hypoxia-Activated Prodrugs

Abstract: Hypoxia is a prevalent feature of many tumors contributing to disease progression and treatment resistance, and therefore constitutes an attractive therapeutic target. Several hypoxiaactivated prodrugs (HAP) have been developed, including the phase III candidate TH-302 (evofosfamide) and the preclinical agent SN30000, which is an optimized analogue of the well-studied HAP tirapazamine. Experience with this therapeutic class highlights an urgent need to identify biomarkers of HAP sensitivity, including enzymes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 47 publications
2
73
1
Order By: Relevance
“…Interestingly, A549 cells were also more sensitive than UT-SCC-14 to increasing concentrations of evofosfamide (Supplementary Figure 2). The cytochrome P450 oxidoreductase (POR) has previously been identified as major determinant for the sensitivity of hypoxia-activated prodrugs [18, 19]. Therefore, the expression level of POR was determined on the cellular and tumor level by western blotting and immunohistochemistry, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, A549 cells were also more sensitive than UT-SCC-14 to increasing concentrations of evofosfamide (Supplementary Figure 2). The cytochrome P450 oxidoreductase (POR) has previously been identified as major determinant for the sensitivity of hypoxia-activated prodrugs [18, 19]. Therefore, the expression level of POR was determined on the cellular and tumor level by western blotting and immunohistochemistry, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on the activation of HAPs previously demonstrated that cytochrome P450 oxidoreductase is indispensable for several HAPs [18, 19, 25]. However, its relevance for the nitroimidazole mustard evofosfamide is less clear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations